Familiarisation of dry farming practices for the successful crop production in dry tract of Mysore State - Managoli, SP (Journal of Soil and Water Conservation, 2022)
The Dry tract in Mysore State lies in the eastern part and comprises a large proportion of the total area. A Very small percentage of dry tract is covered by irrigation and most of the area is utilised for dry farming. The chief crops grown are Jowar, Ragi, Ground-Nut, Wheat, Bajra and Cotton. The most of the area of this part is entirely at the mercy of nature. Dry farming in this part is the only way amidst the gamble in annul rainfall.